Analisis Keunggulan Bersaing UMKM: Dampak Orientasi Pasar dan Green Product dengan Perilaku Keuangan sebagai Variabel Moderasi - Rahmaniya, Anisa; Nuraeni, Nuraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of market orientation and green products on the competitive advantage of MSMEs, with financial behavior as a moderating variable. The research was conducted on bag and wallet MSMEs in Pasuruan using a quantitative approach. Data were collected through questionnaires and analyzed using moderation regression. The results show that market orientation and green products have a significant effect on competitive advantage. Financial behavior positively moderates the relationship between green products and competitive advantage, but negatively moderates the relationship between market orientation and competitive advantage. The implications of this research highlight the importance of financial behavior in optimizing marketing strategies and green products for MSMEs' competitive advantage.